Association of Helicobacter pylori Status with Fecal Calprotectin and Fecal Occult Blood among Primary Healthcare Attendees in Baghdad, Iraq: A Cross-Sectional Study - Jamil, Hussein Ali (SHIFAA, 2026)
Background: Fecal calprotectin is a marker of gastrointestinal inflammation due to neutrophils; however, there is a lack of evidence about its correlation with H. pylori infection, especially among symptomatic individuals seeking care from primary health centers. Aim: The aim of the study was to compare the levels of fecal calprotectin and the fecal occult blood test among patients with positive and negative H. pylori infection and to assess the association of increased calprotectin level with H. pylori infection. Materials and Methods: In a cross-sectional study that took place in Baghdad from May 2025 to May 2026, patients with gastrointestinal symptoms were recruited. Active H. pylori infection was diagnosed using stool antigen test and ¹³C-urea breath test. Fecal calprotectin was determined as a continuous variable and also at the cut-offs of 50 and 250 µg/g. Results: Results: Out of 268 patients, 133 were H. pylori positive, and 135 were H. pylori negative. The median concentration of fecal calprotectin was significantly higher in H. pylori-positive subjects than in the negative ones (63.0 vs 17.0 µg/g; P